PREVALENCE OF CORONARY ARTERY DISEASE IN SYMPTOMATIC PATIENTS WITH ZERO CALCIUM SCORE UNDERGOING CORONARY CT ANGIOGRAPHY (Iraqi Journal of Medical Sciences, 2016)
Background:Non-invasive coronary angiography is being increasingly performed by computed tomography angiography to assess obstructive coronary artery disease. There is increasing interest in the absence of coronary artery calcification, as a “negative” cardiovascular risk factor. The frequency and clinical relevance of coronary artery disease in patients without coronary artery calcification are unclear.Objective:To assess the presence and the severity of coronary artery disease in symptomatic patients without coronary artery calcification (Calcium score of zero).Methods:One hundred and ten cases (62 females and 48 males) with mean age of 50.4 years with no detection of calcified plaques in the coronary arteries (coronary artery calcification score=zero) were studied. Known or suspected cases of coronary artery disease underwent a coronary computed tomography angiography examination. Calcium score examination was conducted immediately before coronary computed tomography angiography. Degree of stenosis was found by comparing the luminal diameter of the narrowest segment of the artery with that of a more proximal or distal normal segment of the same artery.Results: Stenosis was found in 23/110 patients, giving a prevalence of (20.9%), among the 23 cases with stenosis: the right coronary artery stenosis was found in 19/23 (82.6%), left anterior descending in 11/23 (47.8%) and left circumflex artery in 5/23 (21.7%). Mean percentage of stenosis was highest in right coronary artery (59.9%). In 52.2%, only one vessel was involved, in (43.5%) two vessels were involved and in (4.3%) three vessels were involved. Conclusion:Coronary computed tomography angiography can clearly demonstrate noncalcified atherosclerotic coronary plaques in a large group of patients with suspected coronary artery disease. The absence of coronary artery calcification does not exclude the presence of significant stenosis in symptomatic patients with no coronary Calcium.Keywords :Coronary artery disease, Zero Calcium score, CT coronary angiography
Keywords: Coronary artery disease; Zero Calcium score; CT coronary angiography